An Investigation of Disposal Options for Arsenic Trioxide Produced from Roasting Operations - Lunt D (The Australasian Institute of Mining and Metallurgy, 1991)
Arsenic is classified chemically as a metalloid. That is, it has properties intermediate between those of metals and non-metals. Like non-metals, it combines with many metals to form arsenides (eg arsenopyrite FeAsS, niccolite NiAs, sperrylite PtAs2), but like metals it forms sulphides and oxides (eg realgar AsS, arsenolite As203). Arsenic is distributed widely in the Earth's crust at an average concentration of 1.5 mg/kg and is present in more than 150 minerals.